Excess Deaths During the COVID-19 Pandemic: Implications for US Death Investigation Systems - Stokes, Andrew C.; Lundberg, Dielle J.; Bor, Jacob; Bibbins-Domingo, Kirsten (American journal of public health (1971), 2021)
Quality death investigation is a critical piece of an effective public health system.1 When a person dies, a coroner, medical examiner, or health professional with knowledge of the decedent's medical conditions fills out the death certificate. Accurate cause-of death ascertainment has broad implications for understanding the burden of disease throughout the United States. During the coronavirus disease 2019 (COVID-19) pandemic, vital statistics have had an important role in shaping the public health response, including recommendations for physical distancing and mask wearing, temporary lockdowns, and mobilization of health care systems.2 Racial and socioeconomic disparities in deaths attributed to COVID-19 have shown how structural racism contributed to vulnerability during the pandemic.3Although monitoring death certificates for reference to COVID-19 is a useful method for detecting the mortality associated with severe acute respiratory syndrome coronavirus 2 infection, it is likely to result in an undercount if COVID-19 is missing on death certificates in cases in which COVID-19 contributed to death.4-6 In fact, between 15% and 34% of excess deaths that occurred in 2020 during the COVID-19 pandemic were not directly assigned to COVID-19 on death certificates.7 These deaths likely include COVID-19 deaths not assigned to COVID-19 and indirect deaths related to social and economic consequences of the pandemic.